2015
DOI: 10.1016/j.mayocp.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Intravenous Iron Preparations

Abstract: Intravenous iron therapy is not associated with an increased risk of SAEs or infections. Infusion reactions are more pronounced with IV iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 363 publications
(166 citation statements)
references
References 116 publications
7
152
0
7
Order By: Relevance
“…This is in-line with a meta-analysis which reported the safety of iron formulations in different clinical settings and even more so in the subgroup with patients with HF, where the RR for severe adverse events was 0.45 versus any comparator (95% CI 0.29–0.70) [25]. …”
Section: Cost and Adverse Eventssupporting
confidence: 82%
“…This is in-line with a meta-analysis which reported the safety of iron formulations in different clinical settings and even more so in the subgroup with patients with HF, where the RR for severe adverse events was 0.45 versus any comparator (95% CI 0.29–0.70) [25]. …”
Section: Cost and Adverse Eventssupporting
confidence: 82%
“…iron preparations by Avni et al ., showing that i.v. iron is not associated with an increase in severe adverse events 25. Given its efficacy, dosing flexibility, and safety profile compared with other iron preparations such as iron sucrose and ferric gluconate, i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Modern iron formulations are associated with a low risk of reactions, and they have fewer adverse effects than oral iron in several studies. In the meta-analysis by Avni et al [29]on the adverse effects of intravenous iron, it was shown in 97 clinical trials that there was no increased risk of serious adverse events compared with controls, and in double-blind trials, there was a trend towards fewer reactions (risk ratio [RR] 0.83, confidence interval 0.64–1.03). When compared to oral iron, the rate of gastrointestinal reactions was significantly less, with a RR of 0.55.…”
Section: Risks Of Intravenous Ironmentioning
confidence: 99%
“…Studies show rates of mild reactions are ∼1 in 200 and major reactions are ∼1 in 200,000 [29]. These are not classic allergic reactions but instead due to activation of the complement system [28, 32].…”
Section: Risks Of Intravenous Ironmentioning
confidence: 99%